Employment situation of tourism graduates working in and outside the tourism sector - Costa, Carlos (2013)
This paper looks at the employment situation of Portuguese tourism graduates, particularly to the differences between the work situation of those employed in the tourism sector and those who are working outside this sector. Data was collected through an online questionnaire applied to the Portuguese tourism graduates in Portugal, comparing their salaries, working hours and schedules, contractual situation, hierarchical position and job satisfaction. Results evidenced that the tourism sector is not taking advantage of the available qualified human resources. Moreover, data suggests that tourism graduates employed outside the tourism sector are facing poorer working situations than those graduates employed within this industry.